Social Well-Being in College According to Sociodemographic Factors in Education Students - Ramón Chacón-Cuberos; Asunción Martínez-Martínez; Pilar Puertas-Molero; Virginia Viciana-Garófano; Gabriel González-Valero; Félix Zurita-Ortega (Universidad Autónoma de Baja California, 2020)
This study sought to examine the perceived social well-being of students of educational sciences, based on sociodemographic factors. A non-experimental, ex-post-facto descriptive study was performed by way of a single measurement. The sample comprised 313 college students from different education degrees. The results show that women exhibit greater levels of social coherence and contribution, while students (men and women) that enter university through vocational training or other non-high school routes have greater perceived well-being. It was shown that social integration is greater in more urbanized areas and college students that live with other students display greater social acceptance. In addition, living in rural areas was associated with greater social actualization and coherence as social dynamics are more easily understood. Age correlated negatively with social coherence.